3 - Retours, circulations, installations ? Les reconfigurations du système migratoire ivoiro-burkinabè - Boyer, Florence; Néya, Sihé (Africa Development, 2021)
This article discusses the concepts of return and free movement of people based on data collected in Ouagadougou and the province of Comoé (Burkina Faso) from returnee migrants coming from Ivory Coast, as well as along the railroad linking Ouagadougou to Abidjan. It shows that a return fosters transnational ties and helps to reconfigure the Ivoiro-Burkinabe migratory systems.